Towards an appreciation of symphonic music: the role of the performing theatre - Hagan, Gabriel Acquaah (2011)
A Dissertation submitted to the Department of Architecture, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Architecture.